An evaluation of integrated antenatal care program in Bantul District on 2019 - 2020 - Ayu Cahyaningtyas; Aryanto, Samsu; Hidayati, Titiek (BKM Public Health and Community Medicine, 2021)
Objective: Maternal mortality has become the second cause of women mortality in reproductive ages after HIV/AIDS (WHO, 2019). Bantul District is one of the districts in Yogyakarta which has the highest maternal mortality rate with 20 cases reported in 2020. Based on the result audit of maternal perinatal in Bantul District, it was found that most of the maternal mortality caused by the lack of early detection by health workers and community, caused the referral management leads. This evaluation purpose to identify the implementation and success of an integrated antenatal care program in Bantul District. Method: This evaluation program was using descriptive study design. The evaluation program was conducted in 17 community health centers and health office Bantul District in December 2020 – February 2021. The respondents were 35 people which consisted of the head of community health centers, coordinating midwife and Bantul District health officer. The data were collected using questionnaires. Result: In 17 community health centers, four of them (23,53%) have integrated antenatal care 100%. Eight of community health centers (47,01 %) stated that lack of cooperation by related health workers and lack of time in integrated antenatal care services. Four of the community health centers (23,53 %) stated that the quantity of health workers were limited especially with a large workload. One of the community health centers stated that ambulance drivers are not ready 24 hours (still on call) at the time of antenatal care services. Conclusion: The most of community health centers were felt constrained by the lack of cooperation by related health workers and lack of time in integrated antenatal care services. Improving the quality of integrated antenatal care and strengthening cooperation with related health workers can improve the integrated antenatal care services and prevent maternal mortality in Bantul District.